Pelatihan Qasidah Rebana Sebagai Penguatan Seni Religi Di Kabupaten Agam, Sumatera Barat - Warlan Sukandar (AMMA : Jurnal Pengabdian Masyarakat, 2025)
The preservation of local Islamic-based cultural arts, such as qasidah rebana, plays a crucial role in strengthening the religious identity of the community and resisting the tide of modernization that can erode traditional values. The qasidah rebana training program organized by the DPD PKS of Agam Regency aimed to enhance the artistic skills of the community while also reinforcing religious communal bonds. The training was held on October 13, 2024, and was attended by 15 groups from various sub-districts, totaling 105 participants, the majority of whom were members of majelis taklim (Islamic study groups). The training methods included the delivery of material on the history and philosophy of rebana, techniques for playing different types of rebana instruments, group practice sessions, and an art appreciation segment. Evaluation was conducted through direct observation and brief interviews. The results indicated a significant improvement in participants’ technical skills, self-confidence, and motivation. Participants also expressed high enthusiasm and a strong desire to organize follow-up training independently in their respective areas. This training has proven to be effective not only in enhancing individual capacities but also in strengthening social networks and preserving Islamic cultural heritage at the local level.